Iqbal: an analysis on his life, works and mission - Abdul Razak, Mohd Abbas (International Islamic University Malaysia (IIUM), 2011)

(untitled)
The Islamic world has witnessed the emergence of great number of Muslim scholars that come and go with the passing of time. The names of those who made positive contributions are mentioned till to these days. The poet-philosopher Allama Muhammad Iqbal is one of those great scholars who have left a legacy behind to be followed by other scholars particularly in the area of how to deal with the West. His own reconciliatory approach in dealing between the West and the Islamic world should be an interesting one. Within the confines of this paper, the researcher would like to explore and analyze the life, works and mission of Iqbal. Besides that, the research will also conduct an appraisal on Iqbal.